Nutritional evaluation and consumption of foods among adolescents at risk - Coutinho, Natália Maria Penha; Valões, Emanuella Nunes; Lacerda, Nara Carneiro; Menezes, Dilma Neto de (Rev Rene, 2007)
The objective of this study is to demonstrate the nutritional state and the consumption of foods by adolescents in risky situation, assisted by an NGO. The transversal study was accomplished with a sample of 42 adolescents. The largest share of the group was in the age group from 10 to 14 (78,6%). It was Observed that 57,1% of the adolescents’ families received some type of government assistance. It was possible to notice a larger consumption of energetic foods in the main meals. About 28,6% confirmed not consuming green vegetables and vegetables. The BMI indicates that 4,7% of the adolescents were lower weight, 81% were eutrophic and 14,3% were overweight. The variable age group and nutritional state didn’t demonstrate statistical significance change. This study shows the importance of developing education programs and nutritional intervention for the benefit of a balanced diet and health life style.